Clinical performance and analytical accuracy of a C6 peptide-based point-of-care lateral flow immunoassay in Lyme borreliosis serology - Pietikäinen Annukka; Backman Ida; Henningsson Anna J; Hytönen Jukka (Elsevier, 2022)
We evaluated the analytical accuracy and the clinical performance of a ReaScan+ C6 LYME IgG point-of-care immunoassay (Reagena; index test). Analytical accuracy was evaluated in comparison to a C6 Lyme ELISA™ reference method (Oxford Immunotec) with retrospectively identified serum and CSF samples. The clinical performance was evaluated by using Lyme borreliosis patient and control subject serum and CSF samples. The study was conducted by following the 2015 Standards for Reporting of Diagnostic Accuracy Studies procedure. The sensitivity and specificity of the index test with serum samples were 83% and 91.6%, respectively, when C6 Lyme ELISA™ was used as a reference. The clinical sensitivity of the index test was 97.2%/96.8% for identifying Borrelia specific antibodies in definite/possible Lyme neuroborreliosis. With CSF samples, the clinical sensitivity was 97.2% for definite and 87.1% for possible Lyme neuroborreliosis. The clinical specificity of the assay was 96.1% with serum and 100% with CSF samples.